Ecotoxicological effects of sulfonamide on and its removal by the submerged plant Vallisneria natans (Lour.) Hara. (1st March 2020) - Zhu, Liming; Xu, Houtao; Xiao, Wensheng; Lu, Jianke; Lu, Di; Chen, Xiaoyu; Zheng, Xiaoyan; Jeppesen, Erik; Zhang, Wei; Wang, Liqing
Abstract: The extensive application of sulfonamides (SAs) raises concern regarding its negative environmental effects. In aquatic environments, macrophytes may not only be affected by various pollutants, they may also help to reduce the concentrations in the surrounding environment. We studied both the ecotoxicological effects of sulfonamide (SN) on and its removal by Vallisneria natans (Lour.) Hara, an important submerged macrophyte in Chinese lakes and rivers. The toxic effect and oxidative stress caused by SN resulted in a reduction of total chlorophyll (chl.a and b) and autofluorescence of chloroplast. Meanwhile, the levels of reactive oxygen species (ROS, including O2 − and H2 O2 ) and peroxidase (POD) increased with increasing SN concentration and duration of exposure. After 20 days' exposure, a reduction in the relative growth rate (RGR) and leaf length of V. natans was found under SN stress, but SN had only a weak effect on root length. Although high SN concentrations had toxic effects on the growth of V. natans, the plant was overall resistant to the SN doses that we used. We studied the effect of V. natans on sulfonamide removal in an additional 13-day exposure experiment with focus on the dynamics of dissolved oxygen (DO), the oxidation-reduction potential (ORP) and microbial communities in the water column, as well as in the periphyton on V. natans surfaces. The results show that presence of V. natans significantly improved the SN removal efficiency likely by increasing DO, ORP and bacterial diversity in the water column. The presence of V. natans led to higher relative abundances of Saccharimonadales and Rhizoniales. Lefse analysis showed that Saccharimonadales, Micrococcales, Sphingobacteriales, Bacteroidales, Obscuribacterales, Flavobacteriales, Pseudomonadaceae and Myxococcales, which are considered to be SN-resistant bacteria, increased significantly in the V + S+ ( V. natans and SN) treatment compared with the V + S- ( V. natans and no SN) treatment and V–S+ (no V. natans and SN) treatment. As far as we know, ours is the first study of the ecotoxicological effects of sulfonamide and its removal by submerged vascular plants (here V. natans ). Thus, our results add to the understanding of the antibiotic removal mechanism of macrophytes in freshwater systems and help to clarify the linkages between antibiotics and macrophyte-microbe systems; thereby providing new insight into ecological-based removal of antibiotics in aquatic systems. Graphical abstract: Image 1 Highlights: Ecotoxicological effects of sulfonamide and its removal by V. natans were studied for the first time. Sulfonamide influenced the autofluorescence of chloroplast, ROS and POD in the leaves of V. natans. V. natans improved the efficiency of sulfonamide removal in the water column. Higher ORP, DO and bacterial diversity likely favoured the removal of sulfonamide. The microbial community in the water column and on the surface of V. natans changed significantly after the addition of SN.